Fire, drought and flooding rains: The effect of climatic extremes on bird species' responses to time since fire. (18th May 2021) - Connell, Jemima; Hall, Mark A.; Nimmo, Dale G.; Watson, Simon J.; Clarke, Michael F.
Abstract: Aim: Climatic extremes and fire affect ecosystems across the globe, yet our understanding of how species are influenced by the interaction of these broadscale ecological drivers is poorly understood. Using a ten‐year dataset, we tested how extreme drought and rainfall interacted with time since fire (TSF) to shape bird species' distributions. Location: Semi‐arid mallee woodlands of south‐eastern Australia. Methods: We quantified the effects of climatic extremes on bird species' occurrence, species richness and incidence at 180 sites across three climatic periods—an El Niño‐associated drought (the "Big Dry"), immediately after La Niña drought‐breaking rainfall ("Big Wet") and three years following the La Niña event ("Post‐Big Wet"). We then compared species' responses with TSF across the three climatic periods using a chronosequence of sites from 1 to 117 years post‐fire. Results: La Niña rainfall had sustained impacts on species' occurrence. Over half of species increased significantly during the Big Wet. Despite three intervening years of below‐average rainfall, three quarters of these species remained comparably high, Post‐Big Wet. By contrast, less than half of threatened and declining species benefited from high rainfall. Responses of species to TSF were found to differ contingent on climatic conditions: almost twice as many species responded to TSF during the Big Wet and almost three times as many Post‐Big Wet, compared with the Big Dry. Across climatic periods, a majority of species showed preference for mid to older post‐fire vegetation. Main conclusions: Variation in responses to TSF is likely due to the effect of climatic variation on resources. We suggest that, at sites of different post‐fire age, interactions between TSF and climate may differentially influence both the availability and longevity of resources. Given climatic extremes are predicted to become increasingly severe with climate change, accounting for their influence on fauna–fire dynamics will require careful management of fire.